Risk of graft-versus-host disease with rituximab-containing conditioning regimens in allogeneic hematopoietic stem cell transplant. (June 2017) - Marini, Bernard L; Markstrom, Denise; Frame, David
Graft-versus-host disease represents a major cause of morbidity and mortality in allogeneic hematopoietic stem cell transplant patients. There is growing evidence that B lymphocytes may play a role in the pathogenesis of acute graft-versus-host disease. The purpose of this retrospective cohort study was to evaluate the efficacy of rituximab-containing conditioning regimens in decreasing graft-versus-host disease in allogeneic hematopoietic stem cell transplant patients who received standardized tacrolimus-based graft-versus-host disease prophylaxis regimens. Patients were divided into two cohorts, based on the presence (RTX, n  = 54) or absence (No-RTX, n  = 105) of rituximab in the conditioning regimen and were matched 1:2 for major graft-versus-host disease risk factors. The incidence of grade II–IV acute graft-versus-host disease was not different between the two groups (37% vs. 26%, p  = 0.147). When restricting the analysis to recipients of peripheral blood hematopoietic stem cell transplants, the RTX group had a higher incidence of grade II–IV acute graft-versus-host disease, relapse, or death prior to day 100 (55% vs. 36%, p  = 0.037). The median time to the onset of acute graft-versus-host disease was no different between the RTX and No-RTX groups (67 vs. 74 days, respectively, p  = 0.141). Inhibition of antigen presentation by B cells with rituximab-based conditioning regimens does not appear to reduce the incidence of acute graft-versus-host disease in allogeneic hematopoietic stem cell transplant recipients.